Environmental flow in Sri Lanka: ancient anicuts versus modern dams - Silva, E.I.L.; Manthrithilake, Herath; Pitigala, D.; Silva, E.N.S. (Sri Lanka Journals Online, 2014)
Environmental flow describes the stream flow (quantity and regime) required to sustain upstream and downstream habitats, riparian vegetation, human livelihoods and wildlife. When natural rivers or tributaries are held back by weirs, anicuts, barrages or dams, for a variety of purposes such as diversion for irrigation, hydropower generation or flood control often the downstream flow requirement is ignored or neglected. Although there is no universally accepted definition, convention or law on environmental flow, it has been now recognized that environmental flow is essential for sustainability of riparian ecosystem and their services, which are essential for our own existence, livelihoods and many more. This paper looks at physical structures constructed across rivers and tributaries in Sri Lanka since ancient times to date (including mini-hydro power stations) with a view to understand whether simple ancient wisdoms are more appropriate than modern structures for nature conservation. There are tangible evidence to defend that the ancient anicuts known as “amuna” surged sufficient water in tributaries and rivers, to sustain the environment than modern engineering works which has created dead river beds immediately downstream in many streams and rivers.